Schematic Structure of National Data Harmonization System for Identity Management - Festus, Osuolale, A.; Sunday, Adewale, O.; Jeremiah, Abimbola, O. (European Scientific Journal, ESJ, 2017)
Imagine a web-application in which a user can query varieties of information about an individual (like name, age, state of origin, driver’s license number, national identification number, etc.). This information would be stored on different databases, each having its own schema. Often times, these resources are replicated in different locations and on different platforms. Hence, the need for data harmonization or integration. Data harmonization addresses this issue by considering these external resources as materialized views over a virtual mediated schema resulting in “virtual data integration”. When mediated schema is queried, the solution transforms the result into appropriate queries over the various and existing data sources. This paper focuses on data harmonization that cuts across different governmental database and incorporating them all into a centralized view and this is possible as a result of development and implementation of a webbased databank application.